Liquid Cathode Glow Discharge as a Microplasma Excitation Source for Atomic Emission Spectrometry for the Determination of Trace Heavy Metals in Ore Samples. (2nd September 2018) - Yu, Jie; Zhu, Shuwen; Lu, Quanfang; Zhang, Zhichao; Sun, Duixiong; Zhang, Xiaomin; Wang, Xing; Yang, Wu
ABSTRACT: A novel liquid cathode glow discharge (LCGD) was designed as a microplasma excitation source for atomic emission spectrometry (AES) and used for the determination of Pb, Cu, and Cd in digested ore samples. The operating parameters and stability of LCGD-AES were investigated in detail. The statistical analysis ( t -test) was used for comparing the results of ore samples using LCGD-AES and inductively coupled plasma atomic emission spectrometry (ICP-AES). The results showed that the optimized analytical conditions are 650 V discharge voltage, 4.5 mL min −1 solution flow rate, and pH 1 HNO3 as the supporting electrolyte. The limits of detection for Pb, Cu, and Cd were 0.019, 0.47, and 0.37 mg L −1, respectively. The correlation coefficients and relative standard deviations were 0.9985 and 1.19% for Pb, 0.9868 and 2.37% for Cu, and 0.9960 and 3.98% for Cd. The power consumption was below 65 W. The recoveries were in the range from 79.1 to 115.1%. Moreover, the measurement results of ore samples by LCGD-AES are comparable to the values obtained by ICP-AES. Therefore, the LCGD-AES may be developed as a portable analytical instrument for the direct determination of trace heavy metals.